The prevalence and clinical significance of intracranial vertebral artery terminated in posterior inferior cerebellar artery: A multicenter hospital-based study in China - Juehua Zhu; Ruiyun Huang; Kaiwen Ye; Hongbing Chen; Zheng Dai; Yongjun Jiang (Frontiers in Neurology, 2022)
ObjectiveIntracranial vertebral artery terminated in the posterior inferior cerebellar artery (PICA-VA) is the most popular variant of the posterior inferior cerebellar artery, while its prevalence and clinical significance remained unclear. In the present study, we aimed to investigate the prevalence and clinical significance of PICA-VA.MethodsThis was a multicenter hospital-based cross-sectional study. Patients were enrolled for cerebral MRI and MRA within 1 week of stroke onset. Clinical characteristics were recorded. PICA-VA is termed as a vertebral artery that does not communicate with the basilar artery but terminates in an ipsilateral PICA. We observed the prevalence of PICA-VA and identified a relationship between PICA-VA and vertebrobasilar stroke.ResultsFrom 1 August 2015 to 31 May 2017, a total of 2,528 patients were enrolled in the present study. Among them, 95 patients (3.76%, 95/2,528) had the variation of PICA-VA, 51 of which (53.7%) were located on the right side. The prevalence of vertebrobasilar stroke was considerably higher in patients with PICA-VA than those without (40.2%, 37/92 vs. 17.1%, 417/2,436, p < 0.01). PICA-VA was an independent risk for vertebrobasilar stroke after being adjusted for a history of intracranial hemorrhage, diabetes, body mass index, and triglyceride.ConclusionThe present study showed that 3.76% of patients with acute stroke had PICA-VA, which independently increased the risk of acute vertebrobasilar stroke.